2018
DOI: 10.3892/ol.2018.8816
|View full text |Cite
|
Sign up to set email alerts
|

Elevated FUS/TLS expression is negatively associated with E‑cadherin expression and prognosis of patients with non‑small cell lung cancer

Abstract: Fused in sarcoma/translocated in liposarcoma (FUS/TLS), a ubiquitous and multifunctional DNA and RNA-binding protein, contributes an important function in cancer and neurodegenerative disease; however, its role in lung cancer remains unclear. In the present study, the expression of FUS/TLS in non-small cell lung cancer (NSCLC) and the significance of FUS/TLS for predicting the clinical outcome of patients with NSCLC, was examined. FUS/TLS expression was investigated in NSCLC tissues and their matched adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…A total of 15 studies were included, [ 7 , 8 , 10 , 11 , 14 , 15 , 19 , 20 , 22 , 23 , 25 28 , 33 ] containing 616 patients with low differentiation and 1837 patients with medium and high differentiation. There was mild heterogeneity among studies ( I 2 = 65.0%, P < .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 studies were included, [ 7 , 8 , 10 , 11 , 14 , 15 , 19 , 20 , 22 , 23 , 25 28 , 33 ] containing 616 patients with low differentiation and 1837 patients with medium and high differentiation. There was mild heterogeneity among studies ( I 2 = 65.0%, P < .…”
Section: Resultsmentioning
confidence: 99%
“…The RNA-binding-protein FUS, also known as translocated in liposarcoma (TLS), is a critical regulator during the characteristic pathological features of amyotrophic lateral sclerosis (Sun et al, 2015). Recently, studies have found that FUS mRNA or protein expression is upregulated in liposarcoma (Spitzer et al, 2011), breast cancer (Ke et al, 2016), cervical cancer (Zhu et al, 2018), and FUS promotes malignant progression in non-small cell lung cancer (Xiong D. et al, 2018). Functioning as an oncoprotein, FUS has been proven to be essential for the growth of prostate cancer cells by activating androgen receptor signaling (Haile et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Combined with results from starBase and our experiments, FUS was identified as the RBP for LDHB. RBP FUS has been discovered to act as a tumor enhancer in several cancers such as thyroid cancer, non-small cell lung cancer and glioma [26][27][28]. Apart from the verified affinity between FUS and LDHB, it was also revealed that FUS could elevate the stability of LDHB mRNA.…”
Section: Discussionmentioning
confidence: 99%